The Crisis in the Euro Zone : Did the Euro Contribute to the Evolution of the Crisis? - Lin, Justin Yifu; Treichel, Volker (World Bank, Washington, DC, 2012)
The simmering sovereign debt crisis in the Euro Zone represents a looming threat to the recovery of the world economy and could lead to a renewed global financial crisis. The purpose of this paper is to analyze the root causes of the crisis in Europe and assess the extent to which it was driven by the global financial crisis and by factors internal to Europe, notably the adoption of the common currency. Adoption of the euro led to convergence of interest rates in periphery countries to the levels in core countries and, in combination with rising capital inflows owing to greater financial integration, set off a consumption and real estate boom in periphery countries, leading to higher growth and increases in government revenue and spending. The resulting real appreciation led to a loss of competitiveness in periphery countries, adversely affecting export performance and causing rising current account imbalances. While the fiscal position remained manageable before the crisis owing to rising revenue, the recession brought about by the global financial crisis led to the burst of real estate bubbles and a financial sector crisis and to sharply increased budget deficits and worsened debt indicators and triggered the sovereign debt crisis. Core countries, in particular Germany, maintained a competitive edge through wage restraint allowing them to increase exports to periphery countries, while their banks profited from increased lending to non-core countries. In sum, the euro exacerbated intra-European imbalances whose unsustainability became evident in the aftermath of the global financial crisis and triggered the current sovereign debt crisis.